Differences in maximal exercise during running and cycling as a function of mode of exercise for training and competition - Stein, Tyler D. (University of Wisconsin--Whitewater, 2014)
The purpose of this research project was to compare maximal exercise during running and cycling in athletes who train and compete in running, athletes who train and compete in cycling, and athletes who train and compete in both running and cycling. Twenty-three subjects (fifteen males and eight females), including eleven cyclists, seven distance runners and five triathletes, performed graded exercise tests in a randomly assigned order approximately one week apart on a treadmill (Trackmaster) and a computerized cycle ergometer (Velotron, RacerMate, Inc.) using a computerized metabolic analysis system (AEI Technologies/Vacumed). The maximal oxygen consumptions were higher on the treadmill compared to the cycle ergometer for cyclists (51.81 + 10.90 ml/kg/min, 50.61 + 9.32 ml/kg/min), runners (60.20 + 12.95 ml/kg/min, 54.03 + 10.56 ml/kg/min) and triathletes (58.24 + 5.92 ml/kg/min, 53.26 + 10.90 ml/kg/min). These differences were statistically significant only for distance runners (p = 0.0101) and the differences for cyclists were only 1.20 + 4.44 ml/kg/min or 1.50 + 8.90%. The oxygen consumptions at the lactate threshold were higher during the treadmill trials compared to the running trials for cyclists (48.32 + 10.83 ml/kg/min, 45.77 + 8.88 ml/kg/min), runners (53.91 + 14.15 ml/kg/min, 41.44 + 13.69 ml/kg/min) and triathletes (52.7 4 + 5.85 ml/kg/min, 48.82 + 4.49 ml/kg/min). These differences were statistically significant for runners (p = 0.0087) and triathletes (p = 0.0396) and the difference for cyclists was only 2.55 + 5.24 ml/kg/min or 4.12 + 11.50%. The heart rates at the lactate threshold were higher during the treadmill trials compared to the running trials for cyclists (166.7 + 18.0 bpm, 164.5 + 13.4 bpm), runners (175.4 + 6.2 bpm, 159.4 + 23.2 bpm) and triathletes (175.8 + 8.1 bpm, 166.2 + 10.3 bpm). These differences were statistically significant for runners (p = 0.0453) and triathletes (p = 0.0401) and the difference for cyclists was only 2.27 + 9.51 ml/kg/min or 0.97 + 5.97%. For cyclists, the maximal oxygen consumptions, oxygen consumptions at the lactate threshold, and heart rates at the lactate threshold were not statistically different between the treadmill and cycle ergometer. The cycle ergometer provided a mode of exercise that may be preferred by cyclists while performing a graded exercise test to volitional fatigue and offered the distinct advantage of providing power data in Watts with corresponding oxygen consumptions and heart rates that would be advantageous in developing training programs for cyclists and triathletes.
This file was last viewed in Microsoft Edge.
Keywords: Maximal oxygen uptake; Running--Physiological aspects; Cycling--Physiological aspects